Factor structure of the Children’s Depression Inventory in a multisite sample of children and adolescents with chronic pain - Logan, Deirdre E. (2013)
This study examined the factor structure of the Children’s Depression Inventory (CDI) among children and adolescents with chronic pain using exploratory and confirmatory factor analysis in a large, multisite sample of treatment-seeking youth. Participants included 1043 children and adolescents (ages 8–18) with a range of chronic pain complaints who presented for initial evaluation at one of three tertiary care pediatric chronic pain clinics across the U.S. They completed the CDI and reported on pain intensity and functional disability. Factor analysis was conducted using a two-step (exploratory and confirmatory) approach. Results supported a 5-factor model for the CDI with good fit to the data. The distribution and item-total correlations of the somatic items (e.g. pain complaints, fatigue) were explored in this sample. Results indicate that the CDI is a useful tool for assessing depressive symptoms in youth with chronic pain, but some caution is warranted in interpreting the clinical significance of scores in light of the overlap of specific symptoms common to both pain and depression.